(untitled) (Contemporary Journal of Social Science Review, 2024)
This is the age of digital transformation and modernization. The study follows latest digital trends, empirically examines the impact of advertising disclosure and source credibility (i.e., trust, attractiveness, and expertise) on digital behavioral intention from a social media perspective in Pakistan. The respondents of the study were young jobholders from South Punjab, Pakistan who were using digital media platforms. A survey questionnnare was used to collect data from 275 respondents using a convenient sampling technique. The findings indicate that source credibility alongwith its three sub-dimensions and advertising disclosure significantly and positively influence digital behavioral intentions to engage in digital behavior. From both theoretical and practical perspectives, this study offers several contributions: (a) highlights the consequences of online advertising disclosures and source credibility on user intentions related to digital behavior, (b) delivers suggestions for marketing and advertising practices backed by laws, regulations, and policies, and (c) underscores how online advertising disclosures and source credibility provide useful tools and insights for creating successful strategies.